Medium-Distance GPS Ambiguity Resolution with Controlled Failure Rate - Odijk, D; Verhagen, S; Teunissen, Peter (Springer, 2012)
The goal of Network RTK is to provide users with precise ionospheric corrections in order to conduct fast GPS ambiguity resolution and to get cm-level positioning results over medium-distance baselines. In this paper it is shown that a Network RTK user should apply the ratio test with fixed failure rate, having a threshold value that depends on the model at hand, as to test whether the estimated integer solution can be accepted with sufficient more likelihood than the second-best integer solution. Application of the traditional ratio test (with a fixed threshold value) may namely result in too many wrong fixes and consequently severe positioning errors. However, in the paper it is also demonstrated that the ratio test with fixed failure rate should be applied with care, since its correct performance depends on the correctness of the underlying model.